25th Anniversary of Molecules-Recent Advances in Analytical Chemistry - Sanna, Gavino; Tsakovski, Stefan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint gathers 16 contributions (13 research articles and 3 reviews) covering different areas of analytical chemistry. Many of these contributions deal with the development and application in real matrices of chromatographic methods interfaced with mass spectrometry, but also spectroscopic, electrochemical, and separation methods are also proposed.